Developing Hassan bin Ahmed's morphology book and student worksheets using the inductive method at Darul Ihsan Islamic College. - Muthmainnah Muthmainnah; Hilmi Hilmi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
The method of teaching morphology in this institute takes place by reciting the material or reciting it in front of the students, then translating it into the Indonesian language. The school only cares about memorizing the material and lack of exercises. Depending on the interview conducted by the researcher, it indicates that some students feel difficult in using inflection in speech, and they need several language exercises. The research aims to develop Kitab Tashrif by Hasan Bin Ahmad Based on Student Worksheet and Inductive Method and its effects on students. The research method referred to research and development used the method named ADDIE. The researcher has conducted interviews, questionnaires, and tests as research tools. The research population includes all students of a junior high school Darul Ihsan Boarding School in Aceh Besar 789 students in total, and 25 students of class III (A) students are samples. This research aims to develop Arabic listening materials in interactive learning applications that could give more positive benefits for students based on five steps; analysis, design, development, application, and evaluation. As a result, the researcher has successfully created student worksheet based on inductive method. It also has received a positive validation score, 62.5% (very good) in the first stage and 86.25% (Excellent) in the second stage. The application has effectively contributed to the development of students' tashrif ability based on the calculation (ttest), which is bigger than the table's results (ttable) or 2,06 < 11,9 > 2,80.